Photocatalyst assembled based on quantum dots and metal complex as well as preparation method and application of photocatalyst

The photocatalyst assembled by quantum dots and crown ether-modified cobalt phthalocyanine complexes solves the problems of stability and low efficiency of aqueous-phase photocatalytic CO2 reduction, and achieves efficient CO2 reduction performance and a green reaction process.

CN119327513APending Publication Date: 2025-01-21TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310907072.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The stability and efficiency of existing photocatalysts for CO2 reduction in aqueous phase systems are low, and are greatly affected by the competitive reaction of protons.

Method used

A photocatalyst assembled using quantum dots and crown ether-modified cobalt phthalocyanine complexes achieves efficient reduction of CO2 through charge separation at the interface between quantum dots and molecules.

Benefits of technology

The efficient performance of CO2 reduction is achieved in aqueous solution, with TON reaching 49,392 and TOF exceeding 24,000h-1. It does not require organic solvents and the entire reaction process is green, gentle and low-cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327513A_ABST
    Figure CN119327513A_ABST
Patent Text Reader

Abstract

The invention discloses a photocatalyst assembled based on quantum dots and a metal complex as well as a preparation method and application of the photocatalyst. The photocatalyst comprises the following raw materials: a quantum dot solution; the quantum dot solution is prepared from a surface ligand and quantum dots; a metal complex; the metal complex comprises one or more of a metal phthalocyanine complex, a metalloporphyrin complex and a metal bis (dithioalkene) complex; preferably, during assembly, the molar concentration ratio of the quantum dots to the metal complex is 0.5-10. The photocatalyst assembled on the basis of the quantum dots and the metal complexes has the performance of efficient carbon dioxide reduction and the like in an aqueous solution, in addition, the photocatalyst has good applicability in the aqueous solution, no organic solvent needs to be added, the reaction process is green and mild, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and more specifically to a photocatalyst based on the assembly of quantum dots and metal complexes, and a preparation method and application thereof. Background Art

[0002] Photocatalytic reduction of carbon dioxide to fuels and chemical products or nitrite to ammonia is an ideal way to produce valuable chemicals and alleviate environmental pollution. This method directly utilizes inexhaustible solar energy and is carried out under mild conditions. Therefore, it has attracted more and more attention from chemists. Designing and synthesizing efficient photocatalysts is the key to achieving these chemical transformations. For example, in 2017, Kuehnel and his colleagues combined a series of nickel metal complexes ([Ni(terpyX) 2 ] 2+ ) are covalently linked to CdS quantum dots to achieve photoreduction of CO in water 2 The TON of CO is only 20 (J.Am.Chem.Soc., 2017, 139, 7217-7223). In 2018, Lu et al. used CdS quantum dots and binuclear metal cobalt complexes to combine by electrostatic attraction to make the photocatalyst photocatalyze CO in water. 2 The TON of reduction to CO is 1380 (ACS Catal., 2018, 8, 11815-11821). Weiss et al. 2 / ZnS quantum dots and iron metal tetraphenylporphyrin complex (FeTMA) electrostatic assembly to prepare photocatalyst for CO 2 The TON of reduction to CO is 450 and the TOF is 16h -1 (ACS Nano., 2018, 12, 568-575). Erwin et al. covalently linked nickel metal complexes (Ni(cyclam) 2+ ), photocatalytic CO 2 The TON reduced to CO is 121±6 (Chem. Sci., 2021, 12, 9078-9087).

[0003] However, these previous systems are limited by the competitive reaction of protons, and their stability and efficiency of water-phase photocatalytic reactions are low. Therefore, it is necessary to develop an efficient photocatalyst and its application method to achieve water-phase carbon dioxide reduction or nitrite conversion. Summary of the invention

[0004] The first object of the present invention is to provide a photocatalyst based on the assembly of quantum dots (QDs) and metal complexes. The photocatalyst exhibits excellent photocatalytic CO 2Reduction stability and efficiency reveal the photocatalytic CO 2 The photocatalyst assembled from quantum dots and crown ether-modified cobalt phthalocyanine complexes can efficiently capture photons, achieve primary charge separation on an ultrafast time scale, then charge separation at the quantum dot-molecule interface, and final CO reduction via a long-lived charge-separated state. 2 reduction.

[0005] The second object of the present invention is to provide a method for preparing a photocatalyst based on the assembly of quantum dots and metal complexes.

[0006] The third object of the present invention is to provide a photocatalyst based on the assembly of quantum dots and metal complexes for use in aqueous solution photocatalysis.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A photocatalyst based on the assembly of quantum dots and metal complexes, comprising the following raw materials:

[0009] Quantum dot solution; the quantum dot solution is prepared from surface ligands and quantum dots;

[0010] Metal complex; the metal complex includes one or more of metal phthalocyanine complex, metal porphyrin complex, metal bis(disulfide) complex;

[0011] Preferably, during assembly, the molar concentration ratio of the quantum dots to the metal complex is 0.5-10.

[0012] Preferably, the quantum dots are CdSe, CdS, CuInS 2 、ZnSe、CdSe / CdS、CuInS 2 / ZnS、CdS / ZnSe、ZnInS 2 、CuAlS 2 One or more of .

[0013] Preferably, the surface ligand is one or more of tri-n-octylphosphine (oxygen), oleic acid, octadecylamine, 2-mercaptoacetic acid, 3-mercaptopropionic acid (MPA), 2-mercaptoethylamine, glutathione (GSH), and cysteine.

[0014] Preferably, the metal center of the metal complex is one or more of cobalt phthalocyanine, iron phthalocyanine, nickel phthalocyanine, copper phthalocyanine, zinc phthalocyanine and manganese phthalocyanine.

[0015] Preferably, the coordination group of the metal complex is one or more of carboxyl, crown ether, phosphate, thiol, and sulfonate.

[0016] In a second aspect, the present invention provides a method for preparing a photocatalyst based on the assembly of quantum dots and metal complexes, comprising the following steps:

[0017] 1) Take a quantum dot solution, add a dilute acid solution to slowly precipitate it, centrifuge to remove the supernatant, and then wash the precipitate with deionized water;

[0018] 2) The washed quantum dot precipitate is dispersed in an aqueous solution of a metal complex and subjected to ultrasonic treatment for 10-15 minutes to obtain a product.

[0019] In a third aspect, the present invention provides an application of a photocatalyst assembled from quantum dots and metal complexes for photocatalytic reduction of carbon dioxide in an aqueous solution.

[0020] Preferably, the application comprises the following steps:

[0021] An electron sacrificial body is added to an aqueous solution containing a photocatalyst, and carbon dioxide is introduced. Under visible light irradiation conditions, the carbon dioxide is reduced to carbon monoxide.

[0022] Preferably, the molar concentration of the electron sacrificial body in the aqueous solution is 0.1-1 mol / L;

[0023] Preferably, the pH of the reaction solution is 7-8;

[0024] Preferably, the electron sacrificial body comprises NaAsc, IPA, Na 2 SO 3 ,TEOA,TEA,CH 3 OH, BIH, VC, EA, Na 2 One or more of S;

[0025] Preferably, the light source of visible light is an LED lamp, sunlight, a medium-pressure mercury lamp, a high-pressure mercury lamp or a xenon lamp.

[0026] The beneficial effects of the present invention are as follows:

[0027] The photocatalyst assembled by the quantum dots synthesized in the present invention and the metal complex achieves efficient carbon dioxide reduction performance in aqueous solution (TON is 49392) and has the fastest reaction rate (TOF>24000h -1 ), and can also realize the conversion of nitrite into ammonia (33.15μmol). In addition, the photocatalyst has good applicability in aqueous solution, without the need to add organic solvents, and the entire reaction process is green, mild and low-cost.

[0028] The method for assembling a photocatalyst of quantum dots and metal complexes provided by the present invention has the advantages of simple preparation, low cost and good repeatability.

[0029] The photocatalyst assembled from quantum dots and metal complexes provided by the present invention uses steady-state and time-resolved techniques to reveal the full-time and space-time image of the carbon dioxide reduction reaction, clarifying the intrinsic mechanism of the catalytic process. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0031] Figure 1 This is the powder X-ray crystal diffraction spectrum of CdSe quantum dots.

[0032] Figure 2 This is a high-resolution transmission electron microscopy image of CdSe.

[0033] Figure 3 This is the mass spectrum of the cobalt phthalocyanine molecular complex modified with 18-crown-6 ether.

[0034] Figure 4 This is a transmission electron micrograph of the complex of CdSe quantum dots and cobalt phthalocyanine molecules modified with 18-crown-6 ether.

[0035] Figure 5 High-resolution X-ray photoelectron spectroscopy of Cd3d of hybrid photocatalysts of CdSe quantum dots and cobalt phthalocyanine molecular complexes modified with CdSe and 18-crown-6 ether.

[0036] Figure 6 This is a graph showing the changes in the UV-visible absorption spectrum of the aqueous solution of cobalt phthalocyanine complex modified with 18-crown-6 ether before and after adding CdSe quantum dots.

[0037] Figure 7 This is the mass spectrum of the tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex.

[0038] Figure 8 These are ultraviolet absorption spectra of CdSe quantum dots, tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complexes, and CdSe quantum dots and tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complexes.

[0039] Fig. 9 This is a performance graph of the photocatalytic carbon dioxide reduction conversion number changing over time for the photocatalyst assembled with CdSe quantum dots and crown ether modified cobalt phthalocyanine complex.

[0040] Fig.10 This is a graph showing the performance of the photocatalytic carbon dioxide reduction selectivity of the photocatalyst assembled with CdSe quantum dots and crown ether modified cobalt phthalocyanine complexes changing with time.

[0041] Fig.11 UV-visible absorption spectra of different types of quantum dot solutions.

[0042] Fig.12 This is a graph showing the photocatalytic CO2 reduction performance of photocatalysts assembled from different types of quantum dot solutions and crown ether-modified cobalt phthalocyanine complexes.

[0043] Fig.13 This is a performance graph of the photocatalytic carbon dioxide reduction conversion number changing over time for the photocatalyst assembled with CdSe quantum dots and tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex.

[0044] Fig.14 This is a graph showing the performance of the photocatalytic carbon dioxide reduction selectivity of the photocatalyst assembled with CdSe quantum dots and tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complexes changing with time.

[0045] Fig.15 This is a performance graph of the amount of carbon dioxide reduction produced by CdSe quantum dots changing with time.

[0046] Fig.16 This is a performance comparison chart of ammonia generation of cobalt phthalocyanine complex modified with crown ethers in CdSQDs and CdSe / CdSQDs.

[0047] Fig.17 Shown are the excited state decay kinetics and fitting curves of CdSeQDs and cobalt phthalocyanine complexes modified with crown ethers of different concentrations at 750nm.

[0048] Fig.18 Time-resolved luminescence spectra of cobalt phthalocyanine complex modified with crown ether at different concentrations added to CdSeQDs aqueous solution.

[0049] Fig.19 Nanosecond transient absorption spectra of CdSe QDs after adding 10 μM crown ether-modified cobalt phthalocyanine complex.

[0050] Fig. 20 Comparison of the nanosecond transient absorption spectra of the photocatalyst assembled from CdSeQDs and crown ether modified cobalt phthalocyanine complex and the crown ether modified cobalt phthalocyanine complex.

[0051] Fig.21 Nanosecond transient absorption spectra of the photocatalyst assembled from CdSe QDs and crown ether modified cobalt phthalocyanine complexes in Ar and CO2 atmospheres, respectively.

[0052] Fig. 22 Time-resolved luminescence spectra of cobalt phthalocyanine complex modified with tetrakis(4-carboxyphenoxy) added to CdSeQDs aqueous solution at different concentrations. DETAILED DESCRIPTION

[0053] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0054] The synthesis of quantum dots in the present invention can be referred to in the literature. Taking the preparation of CdSe quantum dot solution as an example, the specific preparation process is as follows:

[0055] First, synthesize NaSeSO 3 Solution. Accurately weigh 79 mg (1 mmol) Se powder, 378 mg anhydrous Na 2 SO 3 In a 500mL clean three-necked flask, slowly add 200ml of deionized water, then insert a needle to remove Ar gas for 30min, and then heat under reflux at 120℃ and stir vigorously until the black Se powder is completely dissolved to obtain a colorless and transparent solution, which is then stored away from light. Weigh 184mgCdCl 2 5 / 2H 2 O was placed in a 1000 ml single-necked flask, 760 ml of deionized water was added, followed by 104 μL of 3-mercaptopropionic acid (MPA), and after stirring evenly, 10 M sodium hydroxide solution was added dropwise to adjust the pH of the mixed solution to about 11.0. During this period, the solution changed from clear to white turbidity and then to clear. Subsequently, after bubbling and degassing with a needle for 20 min, 40 ml of freshly prepared NaSeSO was quickly added. 3 The solution was further degassed for 20 min, heated to reflux for 3 h under Ar atmosphere with vigorous stirring to obtain a bright yellow CdSe quantum dot solution.

[0056] like Figure 1 As shown in the figure, the XRD spectrum of CdSe quantum dots shows that the crystal diffraction peaks at 26.2°, 42.5°, and 49.6° belong to the (111), (220), and (311) crystal planes of CdSe quantum dots, respectively, confirming that the synthesized CdSe quantum dots are zinc blende structures (according to the standard card PDFNO.19-0191). At the same time, the sharp peak shape indicates that the prepared quantum dots have good crystallinity. Figure 2 As shown in the results of high-resolution transmission electron microscopy, it can be seen that the synthesized CdSe quantum dots are spherical particles of uniform size. The particle size distribution shows that their average diameter is about 1.9nm. Further measurement of their lattice spacing shows that the lattice spacing of CdSe quantum dots is about Corresponding to the (111) crystal plane of cubic structure quantum dots.

[0057] Preparation of 18-crown-6 ether modified cobalt phthalocyanine complex, the specific preparation process is as follows:

[0058] 1) Synthesis of 4,5-dibromobenzo-18-crown-6(2)

[0059] Accurately weigh 4.3 g of benzo-18-crown-6 (13.8 mmol) in a 250 mL eggplant-shaped bottle, and add about 100 mL of distilled water and stir evenly. Then, slowly drop about 10 mL of concentrated H2O into the suspension at 0 °C. 2 SO 4 . Under vigorous stirring, 5.34 g of N-bromosuccinimide (NBS, 30 mmol) was added to the mixture in small amounts several times. This process took about 15 min. The mixture was stirred at room temperature for 2 hours to obtain a white milky suspension. Then about 30 mL of 3% Na 2 SO 3 Aqueous solution was stirred until the supernatant was colorless. Then saturated NaHCO 3 The aqueous solution was neutralized to pH 7. The precipitate was filtered, washed several times with warm water (3×40 mL), and washed with CH 2 Cl 2 Dissolve and wash with anhydrous Na 2 SO 4 Remove water and concentrate. Column chromatography (silica gel, eluent CH 2 Cl 2 ) to obtain 4.45 g of a white solid (yield: 68.6%). 1 HNMR (400MHz, CDCl 3 )δ7.08(s,2H),4.12(t,4H),3.91(t,4H),3.75(t,4H),3.72(t,4H),3.68(s,4H).

[0060] 2) Synthesis of 4,5-dicyanobenzo-18-crown-6(3)

[0061] 10.1 g (21.5 mmol) of compound 2 and 5.64 g of CuCN (63 mmol) were accurately weighed into a 100 mL two-necked bottle. Under an Ar atmosphere, 50 mL of ultra-dry DMF solution was added with a syringe, and the mixture was heated under reflux for 24 h. After the reaction was cooled, about 100 mL of ammonia water (25%) was poured into the mixture, and air was bubbled for about 30 min. Subsequently, it was extracted three times with dichloromethane and water, each time with an amount of about CH 2 Cl 2 :H 2 O=2:3, and then dried over anhydrous sodium sulfate, concentrated, and purified by column chromatography (silica gel, eluent CH 2 Cl 2 :CH 3OH=40:1) to obtain 4.96 g of a white solid (yield: 63.7%). 1 HNMR (400MHz, CDCl 3 )δ7.14(s,2H),4.22(t,4H),3.94(t,4H),3.75(t,4H),3.71-3.68(t,4H),3.66(s,4H).

[0062] 3) Synthesis of 4,5,4',5',4",5",4"',5"-tetrakis(1,4,7,10,13,16-hexaoxadiene-methylene)metallocobalt phthalocyanine (Ⅱ) (1)

[0063] In a 25 mL two-necked bottle, weigh 2 g (5.5 mmol) of compound 3 and 0.5 g (2 mmol) of Co(OAc) 2 ·4H 2 O solid, under Ar atmosphere, add 5mL N,N-dimethylaminoethanol solution with a syringe, heat and stir under reflux for 24h. After the reactant cools down, wash the solid with about 100mL methanol, and then recrystallize it three times by liquid phase diffusion method to obtain 1.03g of pure dark green solid (yield: 49.7%). Figure 3 As shown, MALDI-TOFMS m / z: theoretical calculation C 72 H 88 CoN 8 NaO 24 [1·Na] + It is 1530.513561 and the test result is 1530.513724.

[0064] The preparation of 4-carboxyphenoxy-modified cobalt phthalocyanine molecular complexes, the specific preparation process is as follows:

[0065] 1) Synthesis of 4-(3,4-dicyanophenoxy)benzoic acid (1)

[0066] 1.63 g 4-chlorophthalonitrile (10 mmol) and 4.14 g p-hydroxybenzoic acid (30 mmol) were accurately weighed in a dry 100 mL eggplant-shaped bottle, 30 mL DMSO was added thereto, and the mixture was stirred at room temperature. Subsequently, K was added to the mixture in batches within 1 h. 2 CO 3 (6.15 g), continue the reaction, and add K after 3 h 2 CO 3 (3.08 g), after 24 h of reaction, K 2 CO 3(3.08g), reacted for 5 days in total. After the reaction, the mixture was poured into 600mL of 1mol / L dilute hydrochloric acid solution, gradually producing flocculent precipitates. Then washed with water several times until neutral, and finally recrystallized with ethanol to obtain white crystals with a yield of 2.01g (yield 76%).

[0067] 2) Synthesis of tetrakis(4-carboxyphenoxy)cobaltphthalocyanine(II) (2)

[0068] Weigh 1.59g of compound 1 (6mmol) and 194.76mg of anhydrous cobalt chloride (1.5mmol) in a 100mL two-necked flask. Under an Ar atmosphere, add 1.8mL of organic base DBU and 45mL of n-pentanol, respectively, and heat to reflux for 12h. After the reaction is cooled to room temperature, add 45mL of ethanol to quench the reaction. Then pour 500mL of 1mol / L dilute hydrochloric acid, filter, and then recrystallize several times to obtain a black solid. Figure 6 As shown, MALDI-TOFMS m / z: theoretical calculation C 60 H 32 CoN 8 O 12 + It is 1115.147 and the test result is 1115.914.

[0069] Example 1

[0070] In this example, a catalyst composed of a CdSe quantum dot solution and a cobalt phthalocyanine complex modified with 18-crown-6 ether was prepared. The specific preparation process is as follows:

[0071] Take 1 mL of the concentrated CdSe quantum dot solution, drop 0.2 mol / L dilute hydrochloric acid solution to slowly precipitate the quantum dots, centrifuge (6500 rpm, 2 min) to remove the supernatant, and then centrifuge the precipitate three times with 2 mL of deionized water (6500 rpm, 3 min) to wash away the residual surface ligands and a small amount of acid on the quantum dots; then disperse the bright yellow precipitate of the CdSe quantum dots from which the ligands were removed in 0.5 mol / L 18-crown-6 ether-modified cobalt phthalocyanine complex, and after 10 minutes of ultrasonic treatment, a transparent yellow-green solution of CdSe quantum dots and crown ether-modified cobalt phthalocyanine hybrid catalyst is formed in situ.

[0072] like Figure 4 As shown in FIG. 1 , it is a high-resolution transmission electron micrograph of the complex of CdSe quantum dots and cobalt phthalocyanine molecules modified with 18-crown-6 ether. Figure 5 As shown in Figure 2, the XPS characterization results of the assembled photocatalyst prepared above. The detailed XPS spectrum of the Cd element shows that the Cd 3d of CdSe QDs has two characteristic absorption peaks, Cd 3d 3 / 2 With Cd 3d5 / 2 They are located at 405.4eV and 412.1eV, respectively, which is consistent with the literature reports. Compared with the single CdSe QDs, after the quantum dots are combined with the cobalt phthalocyanine molecular complex modified with 18-crown-6 ether, the binding energy of Cd 3d moves to the low energy direction by ~0.4eV, indicating that the electron density of the quantum dot Cd increases, because the oxygen atom in the 18-crown-6 ether modified with the cobalt phthalocyanine molecular complex coordinates to the Cd atom of the quantum dot.

[0073] Add CdSe quantum dot solution to the aqueous solution of 18-crown-6 ether modified cobalt phthalocyanine molecular complex, centrifuge and take the supernatant. Figure 6 As shown, the UV-visible absorption spectrum shows that the characteristic absorption peak of the cobalt phthalocyanine molecular complex modified with 18-crown-6 ether completely disappears, indicating that the catalyst in the solution is complexed to the surface of the quantum dots.

[0074] Example 2

[0075] In this example, a catalyst composed of a CdSe quantum dot solution and a 4-carboxyphenoxy-modified cobalt phthalocyanine molecular complex was prepared. The specific preparation process is as follows:

[0076] Take 1mL of concentrated CdSe quantum dot solution, drop 0.2mol / L dilute hydrochloric acid solution to slowly precipitate quantum dots, centrifuge (6500rpm, 2min) to remove supernatant, and wash the precipitate three times with 2mL of deionized water (6500rpm, 3min) to wash away the residual surface ligands and a small amount of acid on the quantum dots. Then disperse the bright yellow precipitate of CdSe quantum dots with ligands removed in 0.5mol / L 4-carboxyphenoxy-modified cobalt phthalocyanine complex, and after about 10min of ultrasonic treatment, a transparent yellow-green CdSe quantum dots and tetra(4-carboxyphenoxy)-modified cobalt phthalocyanine complex hybrid catalyst solution is formed in situ.

[0077] like Figure 8 As shown, the catalyst assembled from the CdSe quantum dot solution and the tetrakis(4-carboxyphenoxy)modified cobalt phthalocyanine complex was characterized by UV-visible absorption spectroscopy. The characteristic Q-band absorption peak of the 4-carboxyphenoxy-modified cobalt phthalocyanine complex in aqueous solution was at 687 nm. After adding CdSe quantum dots, the first exciton absorption peak of the quantum dots appeared in the solution and the Q-band absorption intensity of the 4-carboxyphenoxy-modified cobalt phthalocyanine complex was significantly reduced, indicating that the 4-carboxyphenoxy-modified cobalt phthalocyanine complex in the solution interacted with the quantum dots and complexed to their surface.

[0078] Test Example 1

[0079] A photocatalytic carbon dioxide reduction system based on a CdSe quantum dot solution and cobalt phthalocyanine modified with 18-crown-6 ether was investigated. The specific process is as follows:

[0080] The photocatalyst assembled by 2 μmol / L CdSe quantum dot solution and 0.5 μmol / L cobalt phthalocyanine complex, 0.5 mol / L electron sacrifice NaAsc, was introduced into 4 mL water at a pH of 7.5. 2 The gas was bubbled evenly for 20 min. After the degassing was completed, 300 μL of standard methane (CH 4 ) gas was used as the internal standard. After sealing, the mixture was placed under 440nm blue LEDs for illumination while continuously stirring and connected to circulating condensed water to ensure that the reaction was carried out at room temperature. The generated gas products were qualitatively and quantitatively detected by gas chromatography.

[0081] like Fig. 9 , Fig.10 As shown in the photocatalytic reaction test results, in the initial stage of the reaction, the CO generation rate gradually increased, and the CO generation rate reached the maximum at 45 minutes of reaction, reaching 24453h -1 At the same time, the selectivity of CO gradually increased. The maximum TON of CO reached 49392 after 10h of reaction.

[0082] Test Example 2

[0083] Study on the photocatalytic performance of different types of quantum dot solutions and crown ether modified cobalt phthalocyanine complexes in the photocatalytic CO 2 To restore performance, the specific steps are as follows:

[0084] Take CdS quantum dot solution, CdSe / CdS quantum dot solution, CuInS 2 The photocatalyst assembled from quantum dot solution, 2 μmol / L CdSe / ZnS quantum dot solution and 0.5 μmol / L cobalt phthalocyanine complex, and 0.5 mol / L electron sacrificial body NaAsc were introduced into 4 mL water at a pH of 7.5. 2 The gas was bubbled evenly for 20 min. After the degassing was completed, 300 μL of standard methane (CH 4 ) gas as the internal standard, after sealing, placed under 440nm blue LEDs for illumination, while continuously stirring and connected to circulating condensed water to ensure that the reaction is carried out at room temperature, and the generated gas phase products are qualitatively and quantitatively detected by gas chromatography. The test results are as follows Fig.11 , 12 shown.

[0085] Test Example 3

[0086] Study on the photocatalytic performance of CdSe quantum dot solution and cobalt phthalocyanine complex modified with tetrakis(4-carboxyphenoxy) 2 To restore performance, the specific steps are as follows:

[0087] The photocatalyst assembled from 2 μmol / L CdSe quantum dot solution and 4 μmol / L tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex, and 0.5 mol / L electron sacrificial body NaAsc, was introduced into 4 mL water at a pH of 7.5. 2 The gas was bubbled evenly for 20 min. After the degassing was completed, 300 μL of standard methane (CH 4 ) gas was used as the internal standard. After sealing, the mixture was placed under 440nm blue LEDs for illumination while continuously stirring and connected to circulating condensed water to ensure that the reaction was carried out at room temperature. The generated gas products were qualitatively and quantitatively detected by gas chromatography.

[0088] The photocatalytic reaction test results are as follows Fig.13 , Fig.14 As shown in the figure, after 8 hours of illumination, the TON of CO reached 2714, and the product CO and H 2 The ratio is always maintained at 1:2, which is the ratio of synthesis gas.

[0089] Test Example 4

[0090] Study on the photocatalytic effect of CdSe quantum dot solution on CO 2 To restore performance, the specific steps are as follows:

[0091] 2 μmol / L CdSe quantum dot solution, 0.5 mol / L electron sacrificial body NaAsc, in 4 mL water with a pH of 7.5, CO was introduced 2 The gas was bubbled evenly for 20 min. After the degassing was completed, 300 μL of standard methane (CH 4 ) gas was used as the internal standard. After sealing, the mixture was placed under 440nm blue LEDs for illumination while continuously stirring and connected to circulating condensed water to ensure that the reaction was carried out at room temperature. The generated gas products were qualitatively and quantitatively detected by gas chromatography.

[0092] The photocatalytic reaction test results are as follows Fig.15 As shown, after 6 hours of illumination, only 0.21 μmol CO was generated.

[0093] Test Example 5

[0094] The performance of ammonia generation of cobalt phthalocyanine complex modified by crown ether was investigated in CdS quantum dot solution. The specific steps are as follows:

[0095] Take two 0.382 mL CdS quantum dot solutions (0.27 mg mL -1 ), with or without the addition of 1 μmol / L 18-crown-6 ether-modified cobalt phthalocyanine complex, and 1 mL of electron sacrificial IPA, 1 mL of 0.5 molL -1NaNO 2 The solution was dissolved in 5 mL of water and Ar gas was bubbled evenly for 20 min. After degassing, 300 μL of standard methane (CH 4 ) gas as the internal standard, after sealing, placed under 440nm blue LEDs for illumination, while continuously stirring and connected to circulating condensed water to ensure that the reaction is carried out at room temperature, and the generated gas phase products are qualitatively and quantitatively detected by gas chromatography. The test results are as follows Fig.16 As shown, the results show that adding crown ether-modified cobalt phthalocyanine complex to the CdS quantum dot solution promotes the generation of ammonia.

[0096] Test Example 6

[0097] The ammonia generation performance of cobalt phthalocyanine complex modified by crown ether was investigated in CdSe / CdS quantum dot solution. The specific steps are as follows:

[0098] Same as Experiment 5, except that two 0.55 mL CdSe / CdS quantum dot solutions (0.5 mg mL -1 ), respectively adding or not adding 1 μmol / L 18-crown-6 ether modified cobalt phthalocyanine complex, the test results are as follows Fig.16 As shown, the results show that the addition of crown ether-modified cobalt phthalocyanine complexes to the CdSe / CdS quantum dot solution promotes the generation of ammonia.

[0099] Test Example 7

[0100] Based on the efficient photocatalytic carbon dioxide reduction performance of the photocatalyst assembled from CdSe quantum dot solution and 18-crown-6 ether modified cobalt phthalocyanine complex in aqueous solution, femtosecond transient absorption spectroscopy was used to deeply study the exciton dynamics of CdSe quantum dots and the electron transfer dynamics of the cobalt phthalocyanine molecular complex modified with 18-crown-6 ether. The concentration of all samples was adjusted to 0.2OD and the pump light of 440nm was used as the excitation light source, and the test was carried out in a 1mm quartz cuvette.

[0101] The test results are as follows: Fig.17 As shown in the figure, the addition of 18-crown-6-ether modified cobalt phthalocyanine complex significantly accelerates the decay rate of the excited state of charge capture in quantum dots, indicating that there is a path for electron transfer from the charge separation state to the 18-crown-6-ether modified cobalt phthalocyanine complex. After selecting the kinetic curve at 750nm and fitting it, it can be seen that the photoinduced electron transfer rate is 151ps, which is significantly faster than the recombination of the charge separation state.

[0102] Test Example 8

[0103] In a 2mL aqueous solution of 5μmol / L CdSe quantum dots, 0μmol / L, 1μmol / L, 2μmol / L, 3μmol / L, 4μmol / L, 5μmol / L and 10μmol / L of 18-crown-6 ether modified cobalt phthalocyanine complex were gradually added, and the time-resolved luminescence spectrum was tested with 440nm as the excitation light wavelength.

[0104] Test results such as Fig.18 As shown in the figure, the time-resolved luminescence spectrum verifies the electron transfer process between CdSeQDs and the cobalt phthalocyanine complex modified with 18-crown-6 ether. With the gradual addition of the cobalt phthalocyanine complex modified with 18-crown-6 ether, the fluorescence lifetime at the quantum dot defect gradually decreased from 39.79ns to 28.37ns, and a significant attenuation occurred. The above results prove that a rapid electron transfer process occurred from the charge separation state of the quantum dot to the cobalt phthalocyanine complex modified with 18-crown-6 ether.

[0105] Test Example 9

[0106] Two portions of 10 μmol / L 18-crown-6 ether-modified cobalt phthalocyanine complexes were added or not, and 2 mL of aqueous solution of 5 μmol / L CdSe quantum dots were added, respectively. Both were tested for nanosecond transient absorption spectra using 440 nm as the excitation light wavelength.

[0107] Nanosecond transient absorption spectroscopy test results are as follows Fig.19 As shown, when τ delay When the photoinduced absorption signal of the quantum dots is 10 μs, it completely decays, and a bleaching band is observed at 618 nm. By comparing with the transient absorption spectrum of the excited 18-crown-6 ether-modified cobalt phthalocyanine complex ( Fig. 20 ), indicating that the new transient signal belongs to the reduced 18-crown-6-ether modified cobalt phthalocyanine molecular complex. According to the recovery curve of the bleaching band, the composite lifetime of the interfacial charge separation complex of the quantum dots and the 18-crown-6-ether modified cobalt phthalocyanine complex was calculated to be 1.0ms.

[0108] Test Example 10

[0109] In a 2 mL aqueous solution of 5 μmol / L CdSe quantum dots, 10 μmol / L of 18-crown-6 ether-modified cobalt phthalocyanine molecular complex was added, and the cuvette was sealed and Ar gas or CO was introduced. 2 Degas for 15 to 20 minutes, use 440 nm as the excitation light wavelength, and test the nanosecond transient absorption spectrum.

[0110] Test results such as Fig.21 As shown in CO 2 The bleaching recovery was accelerated under the atmosphere, and the reduced 18-crown-6 ether-modified cobalt phthalocyanine molecular complex and CO were observed.2 The lifetime of the reduced species was significantly reduced to 6.7 μs, indicating that the interfacial charge separation complex of the quantum dots and the 18-crown-6-ether modified cobalt phthalocyanine molecular complex to CO 2 The electron transfer efficiency is 99%, and the rate constant is 4.5×10 6 M -1 s -1 .

[0111] Test Example 11

[0112] In a 2mL aqueous solution of 5μmol / L CdSe quantum dots, 0μmol / L, 2μmol / L, 4μmol / L, and 6μmol / L of tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex were gradually added, and the time-resolved luminescence spectrum was tested with 440nm as the excitation light wavelength.

[0113] Test results such as Fig. 22 As shown, the time-resolved luminescence spectrum verifies the electron transfer process between CdSeQDs and tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex. With the gradual addition of tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex, the average fluorescence lifetime of quantum dots is significantly shortened from 5.92ns to 1.33ns, proving the photogenerated electron transfer process of quantum dots to tetrakis(4-carboxyphenoxy)-modified cobalt phthalocyanine complex.

[0114] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A photocatalyst based on the assembly of quantum dots and metal complexes, characterized in that: Including the following raw materials: Quantum dot solution; the quantum dot solution is prepared from surface ligands and quantum dots; Metal complex; the metal complex includes one or more of metal phthalocyanine complex, metal porphyrin complex, metal bis(disulfide) complex; Preferably, during assembly, the molar concentration ratio of the quantum dot solution to the metal complex is 0.5-10.

2. The photocatalyst according to claim 1, characterized in that The quantum dots are one or more of CdSe, CdS, CuInS2, ZnSe, CdSe / CdS, CuInS2 / ZnS, CdS / ZnSe, ZnInS2, and CuAlS2.

3. The photocatalyst according to claim 1, characterized in that The surface ligand is one or more of tri-n-octylphosphine (oxygen), oleic acid, octadecylamine, 2-mercaptoacetic acid, 3-mercaptopropionic acid (MPA), 2-mercaptoethylamine, glutathione (GSH), and cysteine.

4. The photocatalyst according to claim 1, characterized in that The metal center of the metal complex is one or more of cobalt, iron, nickel, copper, zinc and manganese.

5. The photocatalyst according to claim 1, characterized in that The coordination group of the metal complex is one or more of carboxyl, crown ether, phosphate, thiol and sulfonate.

6. A method for preparing a photocatalyst based on the assembly of quantum dots and metal complexes according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Take a quantum dot solution, add a dilute acid solution to slowly precipitate it, centrifuge to remove the supernatant, and then wash the precipitate with deionized water; 2) The washed quantum dot precipitate is dispersed in an aqueous solution of a metal complex and subjected to ultrasonic treatment for 10-15 minutes to obtain a product.

7. The preparation method according to claim 6, characterized in that: The dilute acid in step 1) is one or more of dilute hydrochloric acid, dilute nitric acid, and dilute sulfuric acid.

8. Use of a photocatalyst based on the assembly of quantum dots and metal complexes as described in any one of claims 1 to 5 for photocatalytic reduction of carbon dioxide in aqueous solution.

9. The use according to claim 8, characterized in that: In an aqueous solution containing a photocatalyst, an electron sacrifice is added, CO2 is introduced, and under visible light irradiation conditions, the reaction produces a reduction product, CO; Preferably, the molar concentration of the electron sacrificial body in the aqueous solution is 0.1-1 mol / L; Preferably, the pH of the reaction solution is 7-8; Preferably, the electron sacrificial body includes one or more of NaAsc, IPA, Na2SO3, TEOA, TEA, CH3OH, BIH, VC, EA, and Na2S.

10. The use according to claim 8, characterized in that: The light source of the visible light is an LED lamp, sunlight, a medium-pressure mercury lamp, a high-pressure mercury lamp or a xenon lamp.